Depression in cirrhosis – a prospective evaluation of the prevalence, predictors and development of a screening nomogram. Issue 2 (28th November 2018) - Buganza‐Torio, Elizabeth; Mitchell, Nicholas; Abraldes, Juan G.; Thomas, Lesley; Ma, Mang; Bailey, Robert J.; Tandon, Puneeta
Summary: Background: Depression is associated with substantial morbidity and mortality in cirrhosis, but is underdiagnosed and undertreated. Aims: Using the Mini International Neuropsychiatric Interview (MINI) as a gold‐standard, to determine prevalence, predictors, and outcomes of depression, and to develop a screening nomogram for use in cirrhosis patients. Methods: Cirrhotic outpatients 18‐80 years of age, not on anti‐depressants, were consecutively recruited from liver clinics at three tertiary care hospitals. Baseline health‐related quality of life (HRQoL) and frailty were determined by the chronic liver disease questionnaire, EQ‐VAS, Clinical Frailty Scale and Fried Frailty Criteria. Depression was identified using the MINI and participants were followed up to 6 months to determine unplanned hospitalization/death. Results: Of 305 patients, 62% were male; mean age 55(10) years; mean MELD 12.5(5), 61% Child Pugh B/C. Prevalence of depression 18% by MINI. Patients with depression had lower baseline HRQoL and higher frailty scores. Five independently predictive factors were used to develop a clinical nomogram for the diagnosis of clinical depression. These included three Hospital Anxiety and Depression Screening tool variables: "I have lost interest in my appearance" (adjusted odds ratio [aOR] 2.2, P  = 0.006), "I look forward with enjoyment to things" (aOR 2.0, P  = 0.02), "I feel cheerful" (aOR 2.8, P  = 0.002), and two demographic variables: younger age (aOR 0.92, P  = 0.001) and not being married or in a common‐law relationship (aOR 0.30, P  = 0.008). Conclusions: Depression is common in patients with cirrhosis. It has a significant impact on HRQoL and functional status. The developed clinical nomogram is promising for the rapid screening of depression in patients with cirrhosis. Abstract : LINKED CONTENT This article is linked to Argent and Smyth paper. To view this article visit https://doi.org/10.1111/apt.15115 .